The Use of Cohesive Devices in Argumentation Essay Writing of English Literature Students - Rullyanti, Merry; Anggeraini, Tri (Universitas Muhammadiyah Prof. DR. HAMKA, 2018)
Writing arguments in an essay is both a challenge and an obstacle for students in writing essays. In fact, students make writing arguments as a constraint due to their lack of understanding of the use of Cohesive Devices in the right writing. The purpose of this study was to analyze the extent to which the use of Cohesive Devices in Unity and Coherence to improve the ability to write Argumentation Essays of English Literature Department students. This research method is quantitative descriptive research. The instruments used in researching Cohesive Devices on Unity and Coherence aspects in argumentation essay are Writing Test, Checklist, Questionnaire, and Interview. The results of the study showed that the ability of English Literature students to write essays in the arguments that were integrated and unity and coherence was at a fairly good level although there were still weaknesses in the selection of transition signals and pronoun references as part of the aspects of Cohesive Devices. Based on observations during the study, students can explain the background of the problem they want to raise in their essay's argument, besides that the use of sentence structure is also quite well controlled by students.  Furthermore, there are some transition signals as part of Cohesive Devices used by students in essay writing arguments in this study, starting with the most commonly used are and, but, because, however, so. Only a few use other transitions such as a result, on the other hand, although. According to Zemach and Rumisek (2015), the use of transitions is sufficient to meet the conditions for using transitions used in argumentation essays and / or cause and effect essays. However, students are still weak in writing essays coherently using cohesive devices especially in using transition signals. These constraints are caused by several things, among others, firstly students still cannot distinguish usage and place the transition signal in the sentence correctly. Second, students still cannot form the right argument by using the correct transition signal in the essay. Apart from that, students still try to express their ideas naturally in writing argumentation essays.